Information about COVID-19 for deaf people: an analysis of Youtube videos in Brazilian sign language - Nelson Miguel Galindo Neto; Guilherme Guarino de Moura Sá; Juliana de Castro Nunes Pereira; Luciana Uchôa Barbosa; Lívia Moreira Barros; Joselany Áfio Caetano (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to analyze YouTube videos with information about COVID-19 in Brazilian sign language. Methods: a cross-sectional study conducted with 402 videos from the YouTube sharing platform. Chi-square, Fisher's exact, Mann-Whitney and Spearman's correlation tests were used. Results: the videos mainly covered COVID-19 prevention (20.6%). There was a positive correlation between video length and number of views (p<0.001). The length of more than 20 minutes was associated with narration only in BSL (p=0.37) and in BSL with audio (p<0.001), while videos with less than 20 minutes were associated with simultaneous narration in BSL, audio and subtitles. Those with narration only in BSL had a similar number of views to those narrated with subtitles and/or audio (p=0.998). Conclusion: the videos were mostly short and included COVID-19 prevention. The longer the video, the greater the number of views. Regardless the presentation of narrations, the videos had a similar number of views.